Integrated application of the geophysics methods in an urban solid waste disposal area in Bauru-SP - Lago, Alexandre Lisboa; Elis, Vagner Roberto; Giacheti, Heraldo Luiz [UNESP] (My University, 2006)
Geophysics has shown effectiveness in identify areas contaminated by urban solid wastes, contributing to become more effective sounding programs directed to collect of samples and installation of monitoring systems. In this context, this work had as purpose evaluating the potentialities of the integration of geophysical methods (resistivity, induced polarization and self-potential) in the environmental characterization of the area of the sanitary landfill of the city of Bauru-SP. The self-potential method allowed to detect the direction of the underground flow. The resistivity and induced polarization methods allowed to identify anomalies inside of the saturated zone, that characterize the presence of contamination generated for the migration of the percolated proceeding of the disposal of solid waste. This contamination is confirmed by direct investigation (chemical analysis of the water collected in the monitoring wells). The geophysical methods used had supplied a great number of information about the several characteristics related to interaction between waste disposal area and environment. ©2006 Sociedade Brasileira de Geofísica.
Aplicação integrada de métodos geofísicos em uma área de disposição de resíduos sólidos urbanos em Bauru-SP
Keywords: Applied geophysics; Electrical methods; Urban solid waste